2018
DOI: 10.1097/aog.0000000000002443
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pharmacologic Treatment of Urgency Urinary Incontinence With Sleep Quality and Daytime Sleepiness

Abstract: Objective To evaluate the association between pharmacological therapy for urgency urinary incontinence (UUI) and sleep quality. Methods It is a planned secondary data analysis of sleep outcomes in a previously conducted multicenter, double-blinded, 12-week randomized trial of pharmacologic therapy for urgency-predominant incontinence among community dwelling women self-diagnosed using the 3-Incontinence Questions (3-IQ) questionnaire. Participants (N = 645) were assigned randomly to antimuscarinic therapy 4–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…2 The economic burden associated with UUI is tremendous, and its negative impact on quality of life is substantial; UUI is associated with increased rates of depression, falls, fractures, and decreased sleep quality. [3][4][5][6] Given the high side effect burden and discontinuation rates for medications, as well as the high failure rate for behavioral therapy, many women ultimately opt for third-line therapy, including intradetrusor injection of onabotulinumtoxinA (BoNT-A). 7 The ideal BoNT-A dose that will simultaneously optimize efficacy for the longest duration and minimize complications for non-neurogenic UUI is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The economic burden associated with UUI is tremendous, and its negative impact on quality of life is substantial; UUI is associated with increased rates of depression, falls, fractures, and decreased sleep quality. [3][4][5][6] Given the high side effect burden and discontinuation rates for medications, as well as the high failure rate for behavioral therapy, many women ultimately opt for third-line therapy, including intradetrusor injection of onabotulinumtoxinA (BoNT-A). 7 The ideal BoNT-A dose that will simultaneously optimize efficacy for the longest duration and minimize complications for non-neurogenic UUI is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is a common condition, impacting up to 30% of women older than 30 years old, with a projected increase in prevalence as the population ages 2 . The economic burden associated with UUI is tremendous, and its negative impact on quality of life is substantial; UUI is associated with increased rates of depression, falls, fractures, and decreased sleep quality 3–6 . Given the high side effect burden and discontinuation rates for medications, as well as the high failure rate for behavioral therapy, many women ultimately opt for third‐line therapy, including intradetrusor injection of onabotulinumtoxinA (BoNT‐A) 7 …”
Section: Introductionmentioning
confidence: 99%
“…Most participants reported the daily use of at least one medication, a finding that might be related to the presence of UI. One study 23 showed that pharmacological treatment of UI improved related symptoms as well as the participants’ sleep quality, demonstrating the relationship between medication use and these two variables. Another study found an association between the development of UI and the use of sleep medications 24 .…”
Section: Discussionmentioning
confidence: 99%